Lynchiatilla Casal, 1963 (Hymenoptera: Mutillidae): a new species from Brazil associated with Paroxystoglossa spiloptera Moure (Hymenoptera: Apidae: Halictinae), and notes on other species - Bergamaschi, Antonio C. B.; Cambra, Roberto A.; Brothers, Denis J.; Melo, Gabriel A. R. (Zootaxa, 2012)
Lynchiatilla parana Cambra in Bergamaschi et al., sp. nov. (female and male) from Brazil and the male of Lynchiatilla leguera Casal, 1963 are newly described and illustrated. Lynchiatilla silvai Casal, 1963 is reported for the first time for the state of Paraná, southern Brazil. A key to the males for those species where they are known is given. Specimens of L. parana sp. nov. were observed and collected during 204 hours of fieldwork in a montane Atlantic Forest area, providing behavioral data and implicating the halictine bee Paroxystoglossa spiloptera Moure, 1960 as its probable host. Adult wasps were captured and kept in individual containers for sex-association mating trials in the laboratory. Color and size variation in a population of L. leguera from Jujuy, northern Argentina, are discussed and illustrated.